Significant differences of lymphocytes isolated from ascites of patients with ovarian cancer compared to blood and tumor lymphocytes. Association of CD3+CD56+ cells with platinum resistance - Bamias, A.; Tsiatas, M. L.; Kafantari, E.; Liakou, C.; Rodolakis, A.; Voulgaris, Z.; Vlahos, G.; Papageorgiou, T.; Tsitsilonis, O.; Bamia, C.; Papatheodoridis, G.; Politi, Ek.; et al. (Gynecologic Oncology, 2007)
Objectives: Tumor infiltrating lymphocytes (TILs) and T regulatory cells (Tregs) have been associated with prognosis in ovarian cancer, but their prognostic significance in ascites has not been studied. We performed a prospective study of T lymphocytes isolated from ascites from patients with ovarian carcinoma and we compared them with the respective populations in blood and tumors. Methods: Mononuclear cells from ascites (n = 71) and blood were isolated by Ficoll, while tumor lymphocytes (n = 20) were obtained upon mechanical dissociation. Phenotypic analysis was performed with flow cytometry. Ascites from 10 patients with cirrhosis was used as control. Results: Tregs containing CD4+CD25+ cells, NK-T containing CD3+CD56+ cells and CD69 and HLADR expression of CD4 and CD8 lymphocytes were significantly increased in tumor ascites compared to blood and control ascites. A selective accumulation of these populations in the ascites of cancer patients, was suggested by the significantly higher ascites/blood (A/B) ratios in cancer patients but not controls. Cancer cell content in ascites was correlated with CD4+CD25+, CD4+CD69+, CD4+HLADR+ and CD8+CD69+ cells. There was no correlation of lymphocyte populations between ascites and samples from peritoneal metastases. Higher tumor grade was associated with increased A/B CD4+CD25+ ratio and reduced CD3+CD56+ cells, while platinum resistance was associated with reduced A/B CD3+CD56+ ratio. Conclusions: There are significant differences of CD3+CD56+ and CD25+CD4+ lymphocytes and increase in lymphocyte activation between blood, ascites and peritoneal metastases from patients with ovarian cancer. The selective accumulation of CD3+CD56+ population in ascites may be a predictive factor for platinum resistance. © 2007 Elsevier Inc. All rights reserved.
Keywords: Immune response; NK-T; Ovarian cancer; Tregs